The Influence of Video Guide to Using the iPosyandu Application on Increasing Recording and Reporting Skills for Cadres in Purwarkarta Regency - Fabianti, Vanny; Rinawan, Fedri Ruluwedarata; Arisanti, Nita; Fitriana, Lisna Anisa; Rohaedi, Slamet (Jurnal Pendidikan Keperawatan Indonesia, 2023)
The iPosyandu application is an innovation in the health sector in the form of mobile technology to assist cadres in recording and reporting. Implement cadres can record and report using iPosyandu. Video as a communication channel for the diffusion of innovations is an attempt to convey messages so that the knowledge, attitudes, and skills of someone who watches the video change. The study aimed to identify the effect of video guides on cadre skill improvement in recording and reporting using the iPosyandu application. The pre-post test study in 120 cadres in Purwakarta Regency was divided into two groups, 60 cadres in the intervention group and 60 in the control group. The intervention group received modules and videos on using the iPosyandu application, while the control group only received modules on using the iPosyandu application. iPosyandu recording and reporting skills using observation sheets. The study shows that video guide influences improving the skills of cadres when using the iPosyandu application (p0.001). Video as a media guide that suits the needs of cadres and media experts can affect the skills of cadres in recording and reporting through iPosyandu.